Appl1 and Appl2 are Expendable for Mouse Development But Are Essential for HGF‐Induced Akt Activation and Migration in Mouse Embryonic Fibroblasts. Issue 5 (21st October 2015) - Tan, Yinfei; Xin, Xiaoban; Coffey, Francis J.; Wiest, David L.; Dong, Lily Q.; Testa, Joseph R.
Abstract : Although Appl1 and Appl2 have been implicated in multiple cellular activities, we and others have found that Appl1 is dispensable for mouse embryonic development, suggesting that Appl2 can substitute for Appl1 during development. To address this possibility, we generated conditionally targeted Appl2 mice. We found that ubiquitous Appl2 knockout ( Appl2−/− ) mice, much like Appl1−/− mice, are viable and grow normally to adulthood. Intriguingly, when Appl1−/− mice were crossed with Appl2−/− mice, we found that homozygous Appl1;Appl2 double knockout (DKO) animals are also viable and grossly normal with regard to reproductive potential and postnatal growth. Appl2‐null and DKO mice were found to exhibit altered red blood cell physiology, with erythrocytes from these mice generally being larger and having a more irregular shape than erythrocytes from wild type mice. Although Appl1/2 proteins have been previously shown to have a very strong interaction with phosphatidylinositol‐3 kinase (Pi3k) in thymic T cells, Pi3k‐Akt signaling and cellular differentiation was unaltered in thymocytes from Appl1;Appl2 (DKO) mice. However, Appl1/2 ‐null mouse embryonic fibroblasts exhibited defects in HGF‐induced Akt activation, migration, and invasion. Taken together, these data suggest that Appl1 and Appl2 are required for robust HGF cell signaling but are dispensable for embryonic development and reproduction. J. Cell. Physiol. 231: 1142–1150, 2016. © 2015 Wiley Periodicals, Inc.